Impact of previous depression on the risk of suicide among prostate cancer patients. (2nd January 2023) - Friberg, Anne Sofie; Carlsson, Sigrid V.; Vickers, Andrew J.; Dalton, Susanne Oksbjerg; Larsen, Signe Benzon; Saltbæk, Lena; Høeg, Beverley Lim; Envold Bidstrup, Pernille; Helgstrand, Thomas; Røder, Andreas; Brasso, Klaus; Johansen, Christoffer
Abstract: Background: Prior studies of suicide risk among prostate cancer patients are conflicting. We compared the risk of suicide in prostate cancer patients to cancer-free men including adjustment for clinical stage, socioeconomic position, somatic comorbidity, and previous depression. Materials and methods: A cohort of 37, 527 men diagnosed with prostate cancer in Denmark during 1998–2011 was identified in the Danish Prostate Cancer Registry (DaPCaR) and compared with 357, 384 cancer-free men matched by age at the time of diagnosis. The primary outcome was death from suicide. Data were analyzed using cumulative incidence functions and multivariable Cox regression models. Results: Among prostate cancer patients, 3813 had a previous depression, defined as filed antidepressant prescription within three years before diagnosis. In the study period, 108 prostate cancer patients were registered with suicide as the cause of death, hereof 26 with previous depression. There was no difference in the cumulative incidence of suicide between prostate cancer patients and cancer-free men. There was no effect modification of previous depression on the risk of suicide ( p = .12). The hazard ratio (HR) for suicide varied with time since diagnosis. A sensitivity analysis showed that the risk of suicide was highest within the first year of diagnosis where prostate cancer patients had a 1.70-fold increased hazard compared with cancer-free men (95% CI, 1.11–2.59). Men with prostate cancer and previous depression had a three-fold increased hazard for suicide compared with prostate cancer patients without a history of depression (HR 2.84, 95% CI, 1.82–4.45). Conclusion: The absolute risk of suicide is low following a prostate cancer diagnosis. Time since diagnosis and a history of depression was associated with the highest risk of suicide. Healthcare professionals should be aware of an increased risk of suicide among men with previous depression, especially in the immediate aftermath of the diagnosis.